Structural and dynamic evaluation of a test bench for mechanical vibrations using finite elements - Palmeth, Luis Humberto Martinez; Marin, Juan Gonzalo Ardila; Montiel, Diana Carolina Polania (International Journal of Innovative Research and Scientific Studies, 2024)
This numerical study was conducted to assess the experimental bench structure’s adequacy for measuring mechanical vibrations. The bench allows for three types of tests: dynamic imbalance of a single flywheel, dynamic imbalance of dual flywheels, and dynamic imbalance due to defective gears. A CAD (Computer-Aided Design) model of the vibration bench was developed in three distinct configurations. We then conducted structural (static) and dynamic (non-linear) analyses to assess the structural integrity of the bench, its components, and the expected vibration amplitudes during testing. Additionally, the structure’s natural frequencies were determined, and their compatibility with the expected excitation frequencies was confirmed. These assessments were executed using finite element models within the Solidworks Simulation™ framework. The findings indicate that, when designing such machinery, it is crucial to ensure that the vibration modes do not coincide with the excitation frequencies, as this can compromise the experimental results. Consequently, we have proposed and accessed two redesigned versions of the bench to ensure structural integrity and prevent resonance during experimental procedures. The redesigns aim to mitigate the risk of resonance by altering the bench’s structural parameters to shift the natural frequencies away from the range of excitation frequencies. This proactive approach is based on the idea that a big difference between the natural and excitation frequencies lowers the chance of resonance, which makes the results of the experiment more reliable. The enhanced designs were subjected to a series of rigorous simulations to validate their performance, ensuring that they meet the stringent requirements for educational and research applications.